Cortical thinning trajectories across disease stages and cognitive impairment in amyotrophic lateral sclerosis. (October 2020) - Consonni, Monica; Dalla Bella, Eleonora; Contarino, Valeria Elisa; Bersano, Enrica; Lauria, Giuseppe
Abstract: Background: Cortical neuron degenerative process underlying upper motor neuron involvement in amyotrophic lateral sclerosis (ALS) spreads to extra-motor regions as disease progresses. This is associated with cognitive and behavioural worsening in more severe disease stages. However, the clinical variability of ALS patients might reflect different cortical involvement in extra-motor areas. Objectives: To investigate cortical thinning across disease stages in ALS patients accounting for their cognitive/behavioural impairment. Methods: Thirty-six ALS patients (17 with cognitive/behavioural impairment, ALSimp) and 26 healthy controls underwent structural 3T magnetic resonance imaging. Cortical thickness was measured with a region-wise approach. The King's Clinical Staging System was used to determine disease stages. The Jonckheere-Terpstra test tested for trends in cortical thinning and cognitive involvement across disease stages. Results: Significant trends toward cortical atrophy across disease stages were found in bilateral frontal and cingular cortex, left temporal gyrus and right occipital gyrus of ALS patients, consistently with cognitive impairment in phonemic fluency, language, verbal episodic memory and social cognition. Sub-group analyses revealed that ALSimp had specific thinning in the right fronto-temporal insular cortex related to more pronounced cognitive involvement. Conclusion: Looking at ALS patients irrespective of their cognitive phenotype, motor and extra-motor cortical involvement is consistent with neuropathological studies of disease dissemination. Segregating patients according to their cognitive status, a distinctive trajectory of cortical thinning emerged for ALSimp patients, suggesting a specific course distinct to that of the classic ALS phenotype. Highlights: Cortical thinning trajectories across disease stages in ALS. Identification of specific cortical thinning trajectories in ALS subgroups. Right hemisphere involvement in the pathological course of cognitive ALS phenotypes.